The Implementation of Quziz in Vocabulary Learning Activities: Students Perception and Motivation - Brahmana, Arsyan Allbie Armando (RETAIN : Journal of Research in English Language Teaching, 2022)
One of the well-known digital game-based media is called Quizizz. Quizizzis an instructional media that is very helpful in learning and helps students enjoy and have more fun when taking lessons. This research aimsto describe how students’ perception and motivation towards the use of “Quizizz” in the classroom. This research used a qualitative method since it employed a case study. Moreover, the researcher conducts this research in a limited or small-scale study case. The data source in this research is students from one of Junior High School in Surabaya. The researcher used observation and semi-structured interview to get the deeper data from the participants. The participants of this research are eight students from online classes. The researcher uses descriptive data analysis to interpret the transcribed data from the interview. Learning vocabulary using instructional media “Quizizz” succeedsin attracting students' attention to keep them following the lesson. Students’ perception towards the use of Quizizz as a learning media in the classroom gives positive responses. When students are interested in the lesson, they get more motivated and easier for them to understand the materials. This research focuses on how students’ perception and motivation towards digital game-based media "Quizizz" as instructional media to learn English vocabulary in the classroom. Using appropriate and interesting media as a learning tool can help students be more interested and motivated in following the English lessons.